Central giant cell granuloma in a 10-year-old pediatric patient - A rare entity in posterior mandible with CBCT findings: A case report - Divya Jose; Kandasamy Murugan; Anisha Cynthia Sathiasekar; Dhineksh Kumar (Wolters Kluwer Medknow Publications, 2021)
Central giant cell granuloma (CGCG) of bone constitutes about 7% of all benign lesions of the jawbones. CGCG, as described by Jaffe in 1953, is an idiopathic non-neoplastic proliferative lesion. The mandible anterior to the first molar is the frequently affected site, and has a tendency to cross the midline. Though CGCG is a benign reactive osseous lesion, it has been classified into two types based on its clinic-radiologic features into a slow growing asymptomatic, nonaggressive lesion, and an aggressive type encountered in younger patients which is painful and grows rapidly into a large size, perforating the cortex causing root resorption, and has a tendency to recur. We report a rare case of aggressive CGCG with massive destruction in molar region and angle of mandible.